PERILAKU SUPPORTER SEPAKBOLA PSIM YOGYAKARTA - Fradiantika, Vita (Universitas Muhammadiyah Purwokerto, 2014)
This study aims to investigate the behavior of PSIMâs (Perserikatan SepakbolaIndonesia Mataram)supporters. This study used qualitative methods with case studyapproach. Informants used in this study consist of three members of Brajamusti boardand three members of the Maident board. For the triangulation, in this study theBrajamusti President, Chairman of The Maident, and two police officers wereinterviewed. The results showed that Brajamusti and The Maident are behave fanatic inproviding support to PSIM, so that often cause fights between supporters. Factor thatcause the broken of Brajamusti is political that made by certain parties for politicalinterests. The positive impact of these two groups of supporters are their contributionfor buying tickets in every time they watch PSIM, so it can be a financial support. Whilethe negative impact of the two groups of supporters are the unfair competition betweenthemÂ that makes support for PSIM become obscured.Keywords: behavior, football, supporters